Expectations of the students of mechatronics in the conversion of technical training faculties into technology faculties of technology - (:unkn) unknown (ELSEVIER SCIENCE BV, 2010)
In this study, it was aimed to determine the expectations of the students of Marmara University, Technical Training Faculty, The Department of Mechatronic Education in the conversion Technical Training Faculties into Faculties of Technology. The target population of the study was formed by the students of Marmara University, Technical Training Faculty, The Department of Mechatronic Education, and the sample was formed by one hundred students selected randomly from 1(st), 2(nd), 3(rd) and 4(th) grades. In the research, the relational scanning model was used. To prepare the survey questions, ten open-ended questions regarding the conversion into the Faculty of Technology were asked to the students; and then a 20-question Likert-type survey with 5 articles was prepared by analyzing these questions. The data was analyzed by the program of SPSS 15.0, and pie charts on results were provided. According to the data obtained at the end of the study, the conclusions reached were that the title problem of the students of Mechatronic Education must be solved, that Technical Training Faculties cannot benefit from Erasmus and Socrates programs as they have no equivalence in European Union, that appropriate conditions for developing common projects with industry as Mechatronic Education is mostly practical due to the nature of the department, that differences of titles and diplomas the graduates of Technical Training - Department of Mechatronic Education and the students who will graduate from Faculties of Technology during conversion must be corrected with arrangements to be made, and that the diplomas gotten must be accepted outside the country. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: European union; technical education; technology faculty; mechatronic training